2017
DOI: 10.1063/1.4994273
|View full text |Cite
|
Sign up to set email alerts
|

Microwave chirality discrimination in enantiomeric liquids

Abstract: Chirality discrimination is of a fundamental interest in biology, chemistry, and metamaterial studies. In optics, near-field plasmon-resonance spectroscopy with superchiral probing fields is effectively applicable for analyses of large biomolecules with chiral properties. We show possibility for microwave near-field chirality discrimination analysis based on magnon-resonance spectroscopy. Newly developed capabilities in microwave sensing using magnetoelectric (ME) probing fields originated from multiresonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…88 It has been recently brought to our attention that interesting opportunities for efficient enantiodiscrimination (although not directly related to electric-dipole approximation methods) arise from the possibility of applying magneto-electric probing fields to near-field microwave spectroscopy. 149 3.4 Enantio-sensitive non-linear wave-mixing PXCD and EMWS are not the only two relatives in the family of enantio-sensitive phenomena which occur in the electricdipole approximation and follow Rule 1. Although PXCD and EMWS are resonant processes, and oscillations take place in the absence of the driving field, the pseudoscalar g can loosely be interpreted as a second order susceptibility w (2) .…”
Section: Enantio-sensitive Microwave Spectroscopymentioning
confidence: 99%
“…88 It has been recently brought to our attention that interesting opportunities for efficient enantiodiscrimination (although not directly related to electric-dipole approximation methods) arise from the possibility of applying magneto-electric probing fields to near-field microwave spectroscopy. 149 3.4 Enantio-sensitive non-linear wave-mixing PXCD and EMWS are not the only two relatives in the family of enantio-sensitive phenomena which occur in the electricdipole approximation and follow Rule 1. Although PXCD and EMWS are resonant processes, and oscillations take place in the absence of the driving field, the pseudoscalar g can loosely be interpreted as a second order susceptibility w (2) .…”
Section: Enantio-sensitive Microwave Spectroscopymentioning
confidence: 99%
“…The frequency  is defined based on both, spin and orbital, momentums of the fields of MDM oscillations. It was shown experimentally that the chiral structure of near-field ME provides the potential for microwave chirality discrimination in chemical and biological objects [103].…”
Section: Transfer Of Angular Momentum To Dielectric Materials Metals ...mentioning
confidence: 99%
“…In Ref. [97], we have experimental observation of microwave chirality discrimination in liquid samples due to MDM eigenstate chirality. There is an evident correspondence between topological edge modes of MDM oscillations and "external" chirality of inserted objects.…”
Section: Prediction Of Exceptional Points For a Structure Of Mdmsmentioning
confidence: 99%
“…Numerous studies of these properties for MDM structures, both numerical and experimental, are shown in Refs. [35,65,96,97].…”
Section: Pt-symmetry Of Mdms In a Ferrite Diskmentioning
confidence: 99%